ANALISIS FENOMENA EKSISTENSIALISME FIGUR ATTACHMENT PADA KEHIDUPAN MAHASISWA HOMOSEKSUAL DI UNIVERSITAS UDAYANA, BALI - Pradnyani Pratiwi, Ni Made Fina; Kebayantini, Ni Luh Nyoman; Mahadewi, Ni Made Anggita Sastri (JURNAL ILMIAH SOSIOLOGI (SOROT), 2020)
ABSTRACT This study analyzes and describes how the phenomenon of attachment figure in the lives of students with homosexual orientation at Udayana University. Through the analysis conducted, most of the informants who are students with homosexual orientation and their attachment figures have conflicts experience when they acted as etre en soi or etre pour soi, it can happen because one human being will certainly objectify another human being to maintain the subjectivity. Broadly speaking, this attachment relationship can be respects each other’s subjectivity as an individual, but does not always work well and has a positive connotation. The conflict that revealed by Sartre in existentialism between one individual and another is illustrated through the various experiences that have been passed and the existential meanings carried out by students with homosexual orientation at Udayana University and their attachment figures. Keywords: Homosexual Students, Attachment Figures, Existentialism, Existence